Edible Plant Oil: Global Status, Health Issues, and Perspectives - Zhou, Ying; Zhao, Weiwei; Lai, Yong; Zhang, Baohong; Zhang, Dangquan (Frontiers in Plant Science, 2020)
Edible plant oil is an indispensable nutritional resource for human health. Various cultivars of oil-bearing plants are grown worldwide, while the different plant oils have different chemical compositions. The extremely complex components in oils lead to diverse standards for evaluating the quality and safety of different edible plant oils. The environment poses great challenges to the plant oil safety and quality during the entire production and industrial chain including plant cultivation, harvesting, oil processing, and storage. Environmental factors, affecting oil quality, include heavy metal or pesticide residue pollution, insect or harmful microbial infestation, and rancidity. Here, we proposed a whole-industrial-chain monitoring system instead of currently used single-link-monitoring approach to monitor and track the quality and safety of edible plant oil during the entire process of oil production, process and storage. Diverse components in oil and various oil-producing processes are discussed, including plant species, oil yield, composition complexity, environmental factors that degrade oil quality, and a multi-stage monitoring system. This information will provide guidance for monitoring the quality and safety of edible plant oils, which were challenged by the deteriorating environment.